2019
DOI: 10.1039/c9nr01352k
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-induced hot-carrier generation differences in gold and silver nanoclusters

Abstract: In the last thirty years, the study of plasmonic properties of noble metal nanostructures has become a very dynamic research area. The design and manipulation of matter in the nanometric scale demand a deep understanding of the underlying physico-chemical processes that operate in this size regimen. Here, a fully atomistic study of the spectroscopic and photodynamic properties of different icosahedral silver and gold nanoclusters have been carried out by using Time-Dependent Density Functional Tight-Binding (T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 58 publications
7
58
0
Order By: Relevance
“…Introduction.-Time-dependent electronic structure simulations are currently applied to fundamental phenomena at the nanoscale, from spectroscopy [1][2][3][4] and photochemistry [5][6][7][8] to quantum conductance [9][10][11][12][13] and energy transfer in molecules and materials [2,[14][15][16][17]. Despite the insight that these simulations provide, they lack an important ingredient: the radiative energy dissipation for any charge density evolving in time.…”
mentioning
confidence: 99%
“…Introduction.-Time-dependent electronic structure simulations are currently applied to fundamental phenomena at the nanoscale, from spectroscopy [1][2][3][4] and photochemistry [5][6][7][8] to quantum conductance [9][10][11][12][13] and energy transfer in molecules and materials [2,[14][15][16][17]. Despite the insight that these simulations provide, they lack an important ingredient: the radiative energy dissipation for any charge density evolving in time.…”
mentioning
confidence: 99%
“…Single layer hBN is also known as white graphene. It has been well demonstrated that the silver substrate could provide a much narrower width of the resonance curves and also deeper resonance dips [49,50]. Two-dimensional perovskite is sandwiched between the hBN and graphene layers, where its optical property will not be affected due to oxidization and liquid contaminations [51,52].…”
Section: Methodsmentioning
confidence: 99%
“…A similar analysis has been conducted for noble metals in other recent reports. 5,11,15 The population and depopulation dynamics of ground state molecular orbitals (MO) are distinguished with positive and negative population values, indicating hot electron and hot hole generation, respectively. These MO population differences are calculated with respect to the ground-state population at the initial time t = 0 (∆ρ ii =ρ ii (t) − ρ ii (0)).…”
Section: Optical Absorption Spectra and Hot-carrier Distribution On Mg Nanoclustersmentioning
confidence: 99%
“…The absorption cross-section associated with these plasmonic materials is often several orders of magnitude larger than most organic dye molecules. [1][2][3]5 Plasmonic nanomaterials have rapidly found different applications in several fields such as optical-sensors, 6 enhanced spectroscopies, 7 and even biomedical application. 8 Recently, it has been reported that some plasmonic materials are able to effectively produce highly energetic distributions of electron-hole-pair (EHP) excitations upon non-radiative decay associated with dephasing of the plasmonic excitation (Landau damping).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation